FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN UTANG PERUSAHAAN PUBLIK - Farah Margaretha; Yolla Argoeby (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2009)
The purpose of this research is to analyze the effect of leverage. This research was used are 100 non financial firms which listed in Indonesian Stock Exchange during 2000-2007. Independent variables from this research are firm size, asset tangibility, profitability, and firm age. Dependent variable is leverage. The analysis methods was used are multiple regression analysis. The result from this research shows that profitability has related to leverage and firm size, asset tangibility, and firm age is not related to leverage.